Evaluation of the use of adsorbent materials in the removal of nitrogen compounds from gas oil as a pre‐treatment for feeds for fluid catalytic cracking units. (20th July 2016) - Silva, Carlos F. P. M.; Davila, Luiz A.; Junior, Amaro G. B.; Figueiredo, Marcos A. G.; Souza, Wallace C.; Albuquerque, Flavio C.
Abstract: This study was designed to investigate the use of commercial adsorbent materials for the removal of nitrogen compounds from a vacuum gas oil obtained from an industrial atmospheric distillation unit. Two types of adsorbents were tested: a clay developed specifically for the removal of nitrogen compounds from middle distillates (jet fuel and diesel); and a silica used in a variety of industries. Kinetic and thermodynamic equilibrium experiments were conducted at three temperatures: 80, 100, and 120 °C. The variation in the concentration of nitrogen and aromatic compounds was monitored throughout the kinetic adsorption and thermodynamic equilibrium experiments. When an adsorbent/gas oil mass ratio of 0.75 was used, the clay removed around 70 % of the basic nitrogen compounds from the gas oil, while the silica removed 80 % of the same compounds, which are the ones that effectively hamper catalytic cracking. The silica also removed 14.2 % of the aromatic compounds, while the clay only removed 4.1 %. This study shows that it is possible to treat a viscous hydrocarbon feed using an adsorption process to remove nitrogen compounds without the need to dilute the feed. Using a fluidized bed advanced cracking evaluation (ACE) unit, which simulates a fluid catalytic cracking unit on a bench scale, the gas oil treated with silica produced 3 % more liquid petroleum gas (LPG) and 4 % more gasoline, while the gas oil treated with clay produced 2 % more LPG and 3 % more gasoline than the untreated gas oil.